ANALISIS HASIL BELAJAR MATEMATIKA SISWA DITINJAU DARI SELF CONFIDENCE - Rasyiqah, Andriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to analyze students' mathematics learning outcomes in terms of their level of self-confidence. The type of research that will be used is qualitative research with descriptive methods. Data collection techniques were carried out by administering non-test and test instruments. The non-test instrument is in the form of administering a self-confidence questionnaire. The test instrument is in the form of questions with 5 multiple choice questions and 3 description questions. The subjects of this research were 15 class XI SMAIT Az-Zuhra students. Data analysis was carried out using Excel by grouping students' self-confidence levels and calculating students' mathematics learning outcomes. The results of this research show that student self-confidence and mathematics learning outcomes are related. Students in the high self-confidence group had an average percentage of 20%, students in the moderate self-confidence group had an average percentage of 60%, and students in the low self-confidence group had an average percentage of 20%.